Reducing the margin in prostate radiotherapy: optimizing radiotherapy with a general-purpose linear accelerator using an in-house position monitoring system - Arumugam, Sankar; Wong, Karen; Do, Viet; Sidhom, Mark (Frontiers in Oncology, 2023)
Purpose: To study the feasibility of optimising the Clinical Target Volume to Planning Target Volume (CTV-PTV) margin in prostate radiotherapy(RT) with a general-purpose linear accelerator using an inhouse developed position monitoring system, SeedTracker.Methods: A cohort of 30 patients having definitive prostate radiotherapy treated within an ethicsapproved prospective trial was considered for this study. The intrafraction prostate motion and the position deviations were measured using SeedTracker system during each treatment fraction. Using this data the CTV-PTV margin required to cover 90% of the patients with a minimum of 95% of the prescription dose to CTV was calculated using van Herk's formula. The margin calculations were performed for treatment scenarios both with and without applying the position corrections for observed position deviations. The feasibility of margin reduction with real-time monitoring was studied by assessing the delivered dose that incorporates the actual target position during treatment delivery and comparing it with the planned dose. This assessment was performed for plans generated with reduced CTV-PTV margin in the range of 7mm-3mm.With real-time monitoring and position corrections applied the margin of 2.0mm, 2.1mm and 2.1mm in LR, AP and SI directions were required to meet the criteria of 90% population to receive 95% of the dose prescription to CTV. Without position corrections applied for observed position deviations a margin of 3.1mm, 4.0mm and 3.0mm was required in LR, AP and SI directions to meet the same criteria. A mean±SD reduction of 0.5±1.8% and 3±7% of V60 for the rectum and bladder can be achieved for every 1mm reduction of PTV margin. With position corrections applied, the CTV D99 can be delivered within -0.2±0.3 Gy of the planned dose for plans with a 3mm margin. Without applying corrections for position deviations the CTV D99 was reduced by a maximum of 1.1±1.1 Gy for the 3mm margin plan and there was a statistically significant difference between planned and delivered dose for 3mm and 4mm margin plans.This study demonstrates the feasibility of reducing the margin in prostate radiotherapy with SeedTracker sytem without compromising the dose delivery accuracy to CTV while reducing dose to critical structures.